BERTA’ARUF DENGAN TILAWAH LANGGAM JAWA - Arafat, Muhammad Yaser (MAGHZA, 2017)
This paper seeks to study the recitation of the Qur'an with the recitation of Javanese style as an interpretation in the reading. The recitation of the Javanese style is done by reciting the Qur'an by using the rhythm of the spiritual sound art treasury of Sekar Macapat. The recitation of Javanese style is not an insult to the Qur'an. Reading practice is not the same as chanting the Qur'an with the rhythm of Arabic songs, dangdut, punk, hip-hop, and other types of musical genres. the recitation of the Qur'an with the Javanese rhythm derived from Sekar Macapat is a good, beautiful, and more important, suluki. it means that the recitation of Javanese style is an act of reciting the Qur'an as well as a cultured act, which aims to draw closer to Allah Almighty, the Prophet Muhammad (peace be upon him), and to connect himself to the spiritual genealogy of the saints in Java. therefore, I call it "Jawi's recitation," which in Javanese spiritual treasury means one who has understood the real reality (al-Haq).